2002
DOI: 10.1590/s1517-83822002000200017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subinhibitory concentrations of antimicrobials on hydrophobicity, adherence and ultra-structure of Fusobacterium nucleatum

Abstract: Fusobacterium nucleatum is considered a bridge organism between earlier and later colonizers in dental biofilms and a putative periodontopathogen. In Dentistry, antimicrobial agents are used for treatment and control of infectious diseases associated with dental plaque. Antiseptics have been used in association with antibiotics to reduce infections after oral surgeries. In this study, the influence of subinhibitory concentrations (SC) of chlorhexidine, triclosan, penicillin G and metronidazole, on hydrophobici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
7
1
2
Order By: Relevance
“…F. nucleatum (4 × 10 8 CFU) alone, P. gingivalis (10 3 CFU) alone, or F. nucleatum plus P. gingivalis (4 × 10 8 CFU/10 3 CFU) were resuspended in TSB medium for 3 h. The particle sizes of F. nucleatum and P. gingivalis ranged from 342-712 nm and 220-615 nm, respectively, as detected by the Zetasizer Nano-ZS (Fig. 1B), are consistent with previous observations using electron microscopy (EM) [18, 27]. Larger particles ranging from 712-1,281 nm were detected when F. nucleatum was mixed with P. gingivalis , supporting the hypothesis that F. nucleatum physically interacts with P. gingivalis to form aggregates.…”
Section: Resultssupporting
confidence: 89%
“…F. nucleatum (4 × 10 8 CFU) alone, P. gingivalis (10 3 CFU) alone, or F. nucleatum plus P. gingivalis (4 × 10 8 CFU/10 3 CFU) were resuspended in TSB medium for 3 h. The particle sizes of F. nucleatum and P. gingivalis ranged from 342-712 nm and 220-615 nm, respectively, as detected by the Zetasizer Nano-ZS (Fig. 1B), are consistent with previous observations using electron microscopy (EM) [18, 27]. Larger particles ranging from 712-1,281 nm were detected when F. nucleatum was mixed with P. gingivalis , supporting the hypothesis that F. nucleatum physically interacts with P. gingivalis to form aggregates.…”
Section: Resultssupporting
confidence: 89%
“…Although some studies have shown that sub-MICs of both PTZ and MET decreased the formation of biofilm and that CLI may increase the same, our results were not able to demonstrate these effects, probably due to the low number of strains tested (OKAMOTO et al, 2002;DE SOUZA FILHO et al, 2012;DE ANDRADE et al, 2016).…”
Section: Discussioncontrasting
confidence: 96%
“…Sub-inhibitory concentrations of antimicrobials could interfere with cell adhesion, hydrophobicity, motility, and the formation of biofilm. It also may affect other necessary factors for the formation of biofilm, such as the quorum sensing system, which is essential for communication between cells and is essential for proper training and maintenance of biofilm (OKAMOTO et al, 2002;FONSECA et al, 2004;DE ANDRADE et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Perlekatan F. nucleatum pada biofilm (in vitro) berkurang oleh adanya bahan antimikroba seperti kloreksidin, triklosan, penisilin-G dan metronidazol. Dinding sel menjadi irregular akibat penyerapan antimokroba ini pada F. nucleatum, seperti yang terlihat pada Gambar 1 [9].…”
Section: Fusobacterium Nucleatumunclassified